Pembelajaran Sejarah di SMK era revolusi industri 4.0: tantangan dan peluang - Nur Fajar Absor (Jurnal Teori dan Praksis Pembelajaran IPS, 2019)
Vocational High Schools (VHS) are currently facing challenges in the era of Industrial Revolution 4.0, this is responded by the government by issuing one of the regulations, namely Peraturan Dirjen Dikdasmen No. 07/D.D5/KK/2018 which changes the curriculum structure in VHS. One of the subjects affected is Sejarah Indonesia which currently only gets 3 hours in class X. Though history is important to learn for show its identity as a nation. The purpose of this study is to examine the challenges and opportunities that faced on history learning in VHS at the era of Industrial Revolution 4.0, so that the application of history learning becomes effective and efficient. This study uses qualitative method by conducting interviews with four teachers and documents study about regulations of curriculum and reviewing other studies. The results found that teachers can use technology in learning, such as Whatsapp, Instagram, Edmodo, Prezi, documentary films, and visit local cultural heritage sites and museums as a media and source of history learning, so that can also be delivered effectively and efficiently. Finally, the goal of history learning to show its identity as a nation and also the integration of Indonesian nation can remain in the midst at the era of Industrial Revolution 4.0.DOI: 10.17977/um022v4i22019p059